The Macedonian conflict ethnic nationalism in a transnational world - Danforth, Loring M. 1949- (Princeton University Press, 1995)
Examines the Macedonian conflict in light of theoretical work on the construction of national identities and cultures and the invention of tradition. This book analyzes two issues: the struggle for human rights of the Macedonian minority in northern Greece and the campaign for international recognition of the independent Republic of Macedonia